2017
DOI: 10.1111/tid.12718
|View full text |Cite
|
Sign up to set email alerts
|

Colonization with extended‐spectrum beta‐lactamase‐producing Enterobacteriaceae in solid organ transplantation: A meta‐analysis and review

Abstract: Among SOT patients, approximately one in five patients is colonized with ESBL-E, although this finding may be skewed by reporting bias from centers with high ESBL-E prevalence. ESBL-E screening in SOT patients should be considered and evaluated in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…Over the last decade, Gram-negative bacteria have become the focus of attention regarding antibiotic resistance for both the general hospital population and SOT-recipients. A recent systematic review reported that 20% of SOT-recipients are colonized with ESBL-producing Escherichia coli [ 3 ]. Colonization by ESBL-producing isolates is an important risk factor for subsequent infection [ 4 ]; about one in 10 renal transplant recipients (RTR) colonized by ESBL-producing bacteria experiences a urinary tract infection (UTI) caused by these pathogens [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, Gram-negative bacteria have become the focus of attention regarding antibiotic resistance for both the general hospital population and SOT-recipients. A recent systematic review reported that 20% of SOT-recipients are colonized with ESBL-producing Escherichia coli [ 3 ]. Colonization by ESBL-producing isolates is an important risk factor for subsequent infection [ 4 ]; about one in 10 renal transplant recipients (RTR) colonized by ESBL-producing bacteria experiences a urinary tract infection (UTI) caused by these pathogens [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alevizakos et al [14] showed in a meta-analysis an extendedspectrum beta-lactamase-producing Enterobacterales (ESBL-E) rectal colonization rate of 17% among liver transplant recipients and 24% among kidney transplant recipients. Carbapenemaseproducing Enterobacterales (CPE) colonization varies between 2.5% in liver recipients and 10.8% in kidney recipients [15].…”
Section: Discussionmentioning
confidence: 99%
“…A major concern related to decolonization with oral antibiotics is resistance, as it could be associated with further development of antimicrobial resistance to the drugs used [14,15,17,22,27,28]. Colistin resistance in the rectal flora was detected in three liver recipients in the DT group and in one liver recipient in the NDT group, none of whom developed MDR-E infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infections due to Gram-negative bacteria are nowadays the foremost cause of infection, their peak incidence occur early in post-transplant, typically within the first month [1,4,5] . Among these, Gram-negative carbapenem resistant (GNCR) strains associated bloodstream infection (BSIs) are a serious hazard for the patient's life [1,6,7], being rectal colonization with resistant strains associated with the occurrence of BSIs in the early post-transplant period [8][9][10]. There are no clear effective preventive measures to prevent GNCR infections after SOT in colonized patients.…”
Section: Introductionmentioning
confidence: 99%